2016
DOI: 10.1017/s0950268816001217
|View full text |Cite
|
Sign up to set email alerts
|

Time to seroconversion of HBsAg to anti-HBs in individuals who lost HBsAg during follow-up

Abstract: To determine the time to appearance of antibody against hepatitis B surface antigen (anti-HBs) after clearance of hepatitis B surface antigen (HBsAg) in chronically infected individuals, we followed up 3963 cases with positive antibody against hepatitis B e antigen (anti-HBe) from 1991 to 2014. Of these, 101 (67 males, 34 females) lost HBsAg. These serocleared cases were checked every 6-month interval regarding HBsAg, anti-HBs, liver function tests, and liver sonography. Hepatitis B virus DNA was assessed at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
2
2
1
1
Order By: Relevance
“…In the subjects who cleared HBsAg, the majority of patients had persistently undetectable HBV DNA levels during follow‐up; however, we revealed low levels of HBV DNA in 34 (11.2%) patients at the last time of follow‐up and 23 (7.0%) patients had HBV DNA detectable levels at the time of HBsAg clearance (Table ). The HBV DNA detected rate in our study was relatively lower than that of Roushan et al, in which, HBV DNA was detected in 16 (15.8%) out of 101 cases at the time of seroclearance. Other studies found that up to 13.4% of cases had detectable HBV DNA with low viral loads .…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…In the subjects who cleared HBsAg, the majority of patients had persistently undetectable HBV DNA levels during follow‐up; however, we revealed low levels of HBV DNA in 34 (11.2%) patients at the last time of follow‐up and 23 (7.0%) patients had HBV DNA detectable levels at the time of HBsAg clearance (Table ). The HBV DNA detected rate in our study was relatively lower than that of Roushan et al, in which, HBV DNA was detected in 16 (15.8%) out of 101 cases at the time of seroclearance. Other studies found that up to 13.4% of cases had detectable HBV DNA with low viral loads .…”
Section: Discussioncontrasting
confidence: 89%
“…By univariate Cox analysis, we found that HBsAg seroclearance rates were higher in male gender, which was in keeping with a previous study . However, it was an interesting finding that female patients were more likely to produce anti‐HBs than males, which was different with an Iranian study of 101 HBsAg seroclearance patients . In that observation study, the appearance of anti‐HBs was not associated with sex.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Long intervals between HBsAg loss and anti-HBs seroconversion have been reported. (20)(21)(22) Roushan et al (20) reported the cumulative probabilities of anti-HBs seroconversion after HBsAg loss at 1, 2, 3, 4, and 5 years were 8.7%, 24.3%, 37%, 49.1%, and 58%, respectively, in inactive CHB carriers with spontaneous HBsAg loss. Yip et al (21) also reported an increasing proportion of patients with spontaneous or NUC-induced HBsAg loss over time; detectable anti-HBs seroconversion occurred in 37.6% of patients at the time of HBsAg loss, 42.6% within 1 year of HBsAg loss, and 53.1% at any time during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, only very small percentage of CHB patients cleared HBsAg, with or without treatment 13 , 25 . A promising clinical observation is that, for patients who experienced the complete loss of HBsAg after decades of anti-viral treatment, they could generate decent levels of HBsAb 26 , indicating that B cells from HBV patients may still maintain the potential to produce HBsAb. In contrast, it was reported that diminished HBsAg-specific B-cell responses were correlated with HBV persistence 27 .…”
Section: Discussionmentioning
confidence: 99%